From accompaniment to abandonment: unaccompanied migrant minors and adolescents in Andalusia (Spain). - Gutiérrez Sánchez, José David (Centro Scalabriniano de Estudos Migratórios (Brasília), 2025)
The following article aims to analyse how minors and young people who carry out their migration projects accompanied by their parents end up immersed in the protection systems of the region of Andalusia (Spain). After conducting 62 interviews with people who have experienced a migration project, the article focuses on the processes of abandonment between minors and families. The results expose the personal conflicts that are experienced during migratory mourning, institutional reception in child protection centres, and the processes of social inclusion/exclusion in the host society. It is shown that family accompaniment is carried out with the aim of providing protection throughout the migration process up to the destination.
Keywords: Menores emigrantes - Protección, asistencia, etc; Integración social; Abandonment; Foreign minors; Family project; International protection; Reception centres